A class of analytic functions and it`s properties - Ramadan, Salma Faraj (Journal of natural sciences, life and applied sciences, 2021)
(Ramadan & Darus, 2019, p37) recently introduced a new class of analytic functions in the complex plane £ . In this present paper we give sufficient conditions for the functions belonging to this class, coefficient inequalities, Growth and distortion theorem and closure theorem are obtained.